Prevalence and risk factors for respiratory morbidity, among high school students of South India - Mathew, Philip; ER, Indiradevi; UR, Soniya; Poonnen, Shilpa B.; Alex, Sajan T.; Solomon, Sony (International Journal of Research in Medical Sciences, 2017)
Background: The prevalence of asthma and other respiratory diseases among children and adolescents has been on the rise in recent years and this can affect the quality of life and scholastic performance of school students. Therefore, it is essential to find out the actual prevalence of respiratory morbidity among high school students so that we can plan early interventions against this problem. Methods: A cross sectional study was conducted among the students from classes 8 to 10, from a public school in Pathanamthitta district of Kerala state, using a modified American Thoracic Society Questionnaire (ATS-DLD-78-A) to assess respiratory symptoms among general population. Results: The prevalence of cough was 40.8% (95% CI 34.8% to 46.9%) and that of wheeze was found to be 19.6% (95% CI 15.1% to 24.9%). Among the possible risk factors for developing respiratory diseases, it was found that only family history of respiratory problems had a significant association with symptoms of respiratory disease (P = 0.002). Conclusion: The very high prevalence of respiratory symptoms in the study may be due to the fact that the study was conducted during the rainy season in which there is a higher incidence of respiratory infections. But these findings point towards the need to conduct more comprehensive and objective studies on the subject.